2023
DOI: 10.2147/dmso.s397243
|View full text |Cite
|
Sign up to set email alerts
|

Association of Metabolically Healthy Obesity and Risk of Cardiovascular Disease Among Adults in China: A Retrospective Cohort Study

Abstract: Purpose Previous studies have shown that metabolically healthy obesity (MHO) and changes in its status are connected to an increased incidence of cardiovascular disease (CVD). Yet, fewer studies have been conducted in China, especially for the middle-aged and elderly population, a high-risk group. The purpose of the study was to investigate the association between metabolic health status and CVD events. Patients and Methods A total of 46,055 participants were categorize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…The studies were published between 2010 and 2023. Three studies used adult treatment panel III (ATP-III) [ 25 27 ], while others used other definitions like Japanese society of internal medicine [ 6 ], American heart association/National heart, lung, and blood institute [ 24 ], harmonized international diabetes federation (IDF) [ 23 ], World Health Organization [ 28 ], joint interim statement [ 29 ], and IDF [ 30 ] (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The studies were published between 2010 and 2023. Three studies used adult treatment panel III (ATP-III) [ 25 27 ], while others used other definitions like Japanese society of internal medicine [ 6 ], American heart association/National heart, lung, and blood institute [ 24 ], harmonized international diabetes federation (IDF) [ 23 ], World Health Organization [ 28 ], joint interim statement [ 29 ], and IDF [ 30 ] (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…On the one hand, Yen et al [ 78 ] studied 21 subjects with obesity, and all of them experienced some degree of abnormal metabolism. In contrast, the following authors reported different frequencies of subjects with metabolically normal obesity [ [79] , [80] , [81] , [82] , [83] ]. While metabolically abnormal obesity is reported, there is substantial evidence regarding metabolically normal obesity.…”
Section: Discussionmentioning
confidence: 99%
“…1 H), the results of body mass and metabolic biomarkers in the mice from Rajagopalan et al [ 33 ] were analyzed. Obesity was defined as a 20–30% increase in body mass compared to controls [ 41 , 42 ], accompanied by ≥ two abnormal metabolic parameters in fasting conditions [ 11 , 43 , 44 ]: insulin resistance [ 11 , 45 ], hypertriglyceridemia [ 11 , [46] , [47] , [48] ], and total hypocholesterolemia [ 41 , 49 ]. The presence of two positive criteria was classified as moderate abnormal metabolism, while three criteria were indicative of severe abnormal metabolism.…”
Section: Methodsmentioning
confidence: 99%